2018
DOI: 10.3389/fimmu.2018.00747
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies Reactive to Commensal Streptococcus mitis Show Cross-Reactivity With Virulent Streptococcus pneumoniae Serotypes

Abstract: Current vaccines against Streptococcus pneumoniae, a bacterial species that afflicts people by causing a wide spectrum of diseases, do not protect against all pneumococcal serotypes. Thus, alternative vaccines to fight pneumococcal infections that target common proteins are under investigation. One promising strategy is to take advantage of immune cross-reactivity between commensal and pathogenic microbes for cross-protection. In this study, we examined the antibody-mediated cross-reactivity between S. pneumon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 36 publications
2
35
0
Order By: Relevance
“…5 Emerging evidence reveals that rabbits immunized with S. mitis generate IgG antibodies that are reactive with both S. mitis and S. pneumoniae. 4 In line with this, we have recently shown that mouse IgG antibodies specific for S. mitis exhibited cross-reactivity toward S. pneumoniae strains D39 (serotype 2) and TIGR4 (serotype 4). 3 Murine IgG antibodies are heterogeneous consisting of four subclasses (IgG1, IgG2a, IgG2b and IgG3).…”
Section: Introductionsupporting
confidence: 57%
See 3 more Smart Citations
“…5 Emerging evidence reveals that rabbits immunized with S. mitis generate IgG antibodies that are reactive with both S. mitis and S. pneumoniae. 4 In line with this, we have recently shown that mouse IgG antibodies specific for S. mitis exhibited cross-reactivity toward S. pneumoniae strains D39 (serotype 2) and TIGR4 (serotype 4). 3 Murine IgG antibodies are heterogeneous consisting of four subclasses (IgG1, IgG2a, IgG2b and IgG3).…”
Section: Introductionsupporting
confidence: 57%
“…All strains were cultured, harvested, and stored as described previously. 4 To lyse the bacterial cells, a Precellys Lysing Kit and Homogenizer (Precellys 24, Bertin Instruments) was used as per the manufacturer's instructions. After homogenization, the bacterial cell lysate was centrifuged at 1,000 g for 5 min at 4°C and the supernatant was collected and stored at −80°C for further use.…”
Section: Bacterial Culture and Lysismentioning
confidence: 99%
See 2 more Smart Citations
“…They also include the major human pathogen, S. pneumoniae . S. pneumoniae has >99% 16S rRNA sequence identity with S. mitis and S. oralis (810), and with which they exchange capsule biosynthesis and antibiotic resistance genes (11, 12) and show antibody cross-reactivity (13).…”
Section: Introductionmentioning
confidence: 99%